2016
DOI: 10.3390/nu8100660
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bifidobacterium breve on the Intestinal Microbiota of Coeliac Children on a Gluten Free Diet: A Pilot Study

Abstract: Coeliac disease (CD) is associated with alterations of the intestinal microbiota. Although several Bifidobacterium strains showed anti-inflammatory activity and prevention of toxic gliadin peptides generation in vitro, few data are available on their efficacy when administered to CD subjects. This study evaluated the effect of administration for three months of a food supplement based on two Bifidobacterium breve strains (B632 and BR03) to restore the gut microbial balance in coeliac children on a gluten free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
91
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 47 publications
6
91
0
6
Order By: Relevance
“…Probiotic-based therapies have been advocated to restore the balance of a "dysbiotic" or disease-promoting microbiota (6). Overgrowth of Proteobacteria in the small intestine has been reported in patients with active CeD and in those with persistent symptoms after gluten withdrawal (16,23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Probiotic-based therapies have been advocated to restore the balance of a "dysbiotic" or disease-promoting microbiota (6). Overgrowth of Proteobacteria in the small intestine has been reported in patients with active CeD and in those with persistent symptoms after gluten withdrawal (16,23).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a number of strains belonging to the genus Bifidobacterium have been proposed as beneficial supplements for a wide range of health conditions (4). Depletions in bifidobacteria have been noted in patients with CeD (5), and attempts have been made to supplement some strains as a therapy for CeD (3,6). However, despite great public interest in the clinical use of specific probiotic strains for intestinal disorders, there is insufficient mechanistic insight to rationalize consistent recommendations.…”
mentioning
confidence: 99%
“…A plethora of studies have demonstrated that the human microbiome has the potential to affect the pathogenesis of immune diseases, particularly autoimmune diseases in which the immune system fails to distinguish self from non-self proteins and attacks self-tissues. Examples of such diseases include multiple sclerosis (8), rheumatoid arthritis, systemic lupus erythematosus, anti-phospholipid syndrome (10), Crohn's disease (11)(12)(13), ulcerative colitis (14), inflammatory bowel diseases (15,16), coeliac disease (17), and Type 1 Diabetes (T1D) (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a high Firmicutes to Bacteroidetes ratio has been associated with consumption of the Western diet 17 and with adverse metabolic changes that occur with obesity. 38, 39 In contrast, a low Firmicutes to Bacteroidetes ratio has been associated with reduced gut biodiversity 40 and observed in patients with inflammatory bowel disease. 41 While the relative abundance of all Firmicutes and Bacteroidetes did not change in either treatment group, individual Firmicutes taxa tended to decrease while Bacteroidetes taxa increased and were associated with changes along the PC1 axis.…”
Section: Discussionmentioning
confidence: 99%